Correlation Between Physical Activity and Musculoskeletal Disorders Among the Elderly - Nadiyah, Sabrina Fitri; Wardhani, Riska Risty; Rosida, Luluk (Poltekkes Kemenkes Surakarta, 2025)
Background: Engaging in physical activity helps prevent Musculoskeletal Disorders (MSDs) in the elderly, which affect both soft and hard supporting tissues of the limbs. Low physical activity levels in older adults often lead to MSD complaints, especially in the lower back, knees, shoulders, and hands. This study aims to evaluate the correlation of physical activity in the incidence of MSDs among the elderly. Methods: This study employed analytical observational research with a cross-sectional design and purposive sampling technique. The participants consisted of 50 older adults aged 60 and above. The research utilized the Physical Activity Questionnaire-Short Form (IPAQ-SF) to assess physical activity, while musculoskeletal disorders were evaluated using the Nordic Body Map (NBM). Data analysis was performed using the Spearman rank statistical test, facilitated by SPSS version 23 software. Results: The findings showed a notable relationship between physical activity and the occurrence of musculoskeletal disorders in older adults, yielding a p-value of <0.001 and a correlation coefficient of -0.474, indicating a moderate level of strength. This means that the lower a person's level of physical activity, the higher the degree of Musculoskeletal Disorder complaints. Conclusion: This study demonstrates a significant correlation between low levels of physical activity and the prevalence and severity of MSDs among older adults at the Arum Sari Health Post. The findings emphasize the need to raise public awareness and investigate additional risk factors to enhance the prevention and management of MSDs in the elderly.